Preparation And Charaterization Of Rice Husk Biochar-Based Chemical Activated Carbon In Varying Particle Size - Azira Khairudin; Mahfuzah Haji Muhammad; Syahida Suhaimi; Ummu Humairah Hashim; Maisurah Mukhtar; Nur Athirah Mohd Taib; Mohd Ikmar Nizam Mohamad Isa; Azwani Sofia Ahmad Khiar (Karya Ilham Publishing, 2026)
Non-Indexed Publication